KARAKTERISTIK FISIKOKIMIA DAN ORGANOLEPTIK KERUPUK AMPAS TAHU DENGAN PENAMBAHAN IKAN NILA (Oreochromis niloticus) - Aziz, Muhammad; Albaar, Nurjanna; Rasulu, Hamidin (Universitas Khairun, 2024)
Tofu dregs are byproducts generated during the manufacturing of tofu, derived from the pressing and compressing of soybean pulp. A byproduct of tofu production is tofu dregs. The physicochemical and organoleptic characteristics of tofu dregs crackers with the addition of tilapia (Oreochromis niloticus) are the subject of this research. A completely randomized design (CRD), which used 1 factor, 5 treatments and 3 replications, used a mixture of tofu dregs and tilapia fish. The concentrations of tofu dregs and tilapia meat (P) are as follows: 90%: 10%; 80%: 20%; 70%: 30%; 60%: 40%; and 50%:50%. The results indicated that tofu dregs crackers significantly influenced each characteristic assessed: physical (fracture strength and swelling volume), chemical (water, ash, protein, fat, and carbs), and organoleptic (color, taste, scent, and texture) at p 0.05. In this study, treatment P1, which contained 90% tofu dregs and 10% tilapia, had physical test results such as a breaking force of 2.16 N/s and a swelling volume of 14.16%. On the other hand, organoleptic tests of color 3.79, taste 4.28, aroma 4.05, and texture 4.14 were obtained by treatment P1. The panelists found that the tofu dregs crackers treated in treatment P1 were more preferred. Because it meets the SNI requirements for fried crackers, the water content of 11.57% in P3 is the best result.Â Keywords: Tofu dregs, crackers, physicochemistry, organoleptic, tilapia